Effects of the COVID-19 pandemic on mental health, working, and life situation of employees in the Swedish hospitality industry - Feltmann, Kristin; Gustafsson, Nina-Katri J.; Elgán, Tobias H.; Gripenberg, Johanna; Kvillemo, Pia (Frontiers in Public Health, 2023)
Introduction Previous studies reported that the coronavirus disease (COVID-19) pandemic has negatively affected the mental health of employees in the hospitality industry internationally, however, its effect in Sweden has not been studied. Unlike several other countries, Sweden never enforced a lockdown. Restaurants, bars, and hotels could remain open and host a limited number of guests but had to abide by certain restrictions. Methods A cross-sectional survey was distributed among hospitality industry employees containing questions regarding the perceived effects of the pandemic on the respondents’ working and life situations and their physical and psychological health. The sample consisted of 699 individuals, with a response rate of 47.9%. Results Although several respondents had been laid off or furloughed, the majority of the sample remained at the same employer. However, more than half of the respondents reported that their economic situation had deteriorated. Compared to before the pandemic, 38.1% experienced elevated levels of stress, 48.3% experienced elevated levels of worry, and 31.4% reported worsened mood. A deteriorating personal economy and difficulty in following COVID-19-related restrictions at work were associated with the worsening of these three mental health aspects. While the fear of becoming infected with COVID-19 was related to higher levels of stress, the fear of infecting others was related to higher levels of worry. Conclusion Although Sweden imposed less strict measures than most other countries, the personal economy and mental health of hospitality workers were negatively affected by the COVID-19 pandemic.